2017
DOI: 10.4048/jbc.2017.20.1.20
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Nicotinamide Phosphoribosyltransferase Induces Apoptosis in Estrogen Receptor-Positive MCF-7 Breast Cancer Cells

Abstract: PurposeTumor cells have increased turnover of nicotinamide adenine dinucleotide (NAD+), the main coenzyme in processes including adenosine diphosphate-ribosylation, deacetylation, and calcium mobilization. NAD+ is predominantly synthesized in human cells via the salvage pathway, with the first component being nicotinamide. Nicotinamide phosphoribosyltransferase (NAMPT) is the key enzyme in this pathway, and its chemical inhibition by FK866 has elicited antitumor effects in several preclinical models of solid a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
22
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1
1

Relationship

4
3

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 28 publications
6
22
0
Order By: Relevance
“…Here we showed that inhibition of NAMPT and the further decline in NAD levels leads to diminished cell viability and a prominent induction of apoptosis. We had earlier reported that inhibition of NAMPT by its specific inhibitor could effectively reduce NAD levels and induce apoptosis in breast cancer cells (46). In line with our findings, inhibition of NAMPT by microRNAs has also been shown to be an appropriate method in modulating NAD content and cell viability (40)(41)(42).…”
Section: Mir-154 Regulated Nampt By Direct Binding To Its 3′-utrsupporting
confidence: 90%
“…Here we showed that inhibition of NAMPT and the further decline in NAD levels leads to diminished cell viability and a prominent induction of apoptosis. We had earlier reported that inhibition of NAMPT by its specific inhibitor could effectively reduce NAD levels and induce apoptosis in breast cancer cells (46). In line with our findings, inhibition of NAMPT by microRNAs has also been shown to be an appropriate method in modulating NAD content and cell viability (40)(41)(42).…”
Section: Mir-154 Regulated Nampt By Direct Binding To Its 3′-utrsupporting
confidence: 90%
“…Acetylation and phosphorylation are the regulatory mechanisms for p53 stability, and p53 acetylation also activates its sequence‐specific DNA‐binding activity . Inhibition of NAMPT and consequent decrease in cellular NAD levels have been shown to increase p53 acetylation in MCF‐7 breast cancer cells . Considering the importance of p53 as a substrate for SIRT1 and induction of SIRT1 by visfatin, in this study p53 acetylation status was investigated and found to be decreased by visfatin.…”
Section: Discussionmentioning
confidence: 94%
“…Previous studies have shown that NAMPT and miR-494 are involved in cell viability (Alaee et al, 2017[3], Liu et al, 2015[27], Chen et al, 2015[9], Zhang et al, 2013[54]). Viability of the cells was measured using WST-1.…”
Section: Resultsmentioning
confidence: 99%
“…It has been shown that inhibition of NAMPT leads to an induction of apoptosis and reduction of cell survival in cancer cell lines concomitant with the decline in NAD levels (Alaee et al, 2017[3]; Hasmann and Schemainda, 2003[18]; Yang et al, 2007[50]; Holen et al, 2008[21]) . Here we revealed that up-regulation of miR-494 reduced cell viability and induced apoptosis in BC cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation